Pengaruh Sikap Pada Mata Pelajaran Kimia dan Konsep Diri terhadap Prestasi Belajar Kimia - Novrita Mulya Rosa (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2012)
The purpose of this study was to determine the effect of attitude on the subjects of chemistry and self-concept to chemistry learning achievement. Survey research samples totaled 75 students of class X from Private Senior High Sub-district of Cilandak South Jakarta. The data was collected by administering questionnaires and achievement tests to carry out the study. The results showed by the regression equation Y=-12.983 + 0.300 SK + 0.390 KD. Variable attitude on the subjects of chemistry and self-concept of students together to have a significant influence on learning achievement of students, this is indicated by the coefficient determination R2= 0.777 with Fvalue test =125,400 greater than Ftable=3,12. While testing the regression coefficient on the variable attitude o the subject of chemistry t-test = 6,288 and testing the regression coefficients on the self-concept obtained by calculating the t-test=5,397, both are more than t-table=1,993.